A literature review of ecosystem-based strategies to reduce public building vulnerability to earthquakes: A case study of Tarakan City - Eko Prihartanto; Widyo Nugroho; Budi Setiawan (Journal of Engineering Researcher and Lecturer, 2026)
Tarakan City, an archipelagic region in Indonesia, exhibits a high level of vulnerability to earthquake disasters, particularly regarding public infrastructure that has not been fully designed using seismic resilience approaches. Public buildings such as schools, hospitals, and government offices play a vital role in supporting social functions and basic services, making their earthquake resilience highly crucial. This study aims to identify and analyze ecosystem-based strategies that can be employed to reduce the vulnerability of public buildings to earthquakes. Through a systematic literature review method, this research examines various approaches involving technical, social, institutional, and environmental aspects in building infrastructure resilience. The results indicate that the integration of earthquake-resistant building design, community participation, risk-based spatial planning policies, early warning systems, and institutional capacity building forms an effective and sustainable resilience ecosystem. The contextual analysis of Tarakan City suggests the need for synergy between local government, the community, and the technical sector to strengthen the adaptive capacity of public infrastructure, particularly within the context of archipelagic regions facing logistical and resource constraints. This study provides a conceptual framework that can serve as a basis for developing resilient ecosystem-based mitigation policies for earthquake-prone areas.